Details of the Latina Shikhara - Temples of India Project Team (Jio Institute, 2024)
Seen here are the details of the latina shikhara (mono-spire superstructure) of the side shrine from the Triple-shrine Temple. It consists of a broad band as the madhyalata (central band), which is made up of a mesh of gavaksha (chaitya dormer motifs) stacked up in an ascending order. As the shikhara tapers upwards, the chaitya dormer motifs diminish in size. The base of the shikhara is also made up of protruding moulding along with a decorative recess. The bands flanking the madhyalata are thinner and made up of half the designs of the chaitya dormer.